Multimodal imaging of retinal metastasis masquerading as an acute retinal necrosis - Fukutaro Mano; Stephen A. LoBue; Kuo-Chung Chang; Tomiya Mano (International Journal of Retina and Vitreous, 2018)
Abstract Background To report the multimodal imaging and histology of a case of metastatic esophageal cancer with vitreoretinal involvement resembling acute retinal necrosis (ARN) in a patient receiving systemic chemotherapy. Case presentation A 69-year-old Japanese man with a history of stage 4 esophageal carcinoma, treated with three cycles of 5-fluorouracil (5-FU) and cisplatin (CDDP) chemotherapy as well as 30 sessions of radiation therapy, presented with new onset of blurry vision in the right eye (OD). Visual acuity was 20/200 OD. Fundus examination OD revealed 2+ nuclear cataract, veil-like vitreous opacity, a tractional retinal detachment, and white retinal lesions in the macula and periphery masquerading as an ARN. Due to the poor view and uncertainty regarding diagnosis, combined cataract extraction and 25 gauge pars plana vitrectomy was performed. Polymerase chain reaction and cytologic analysis were performed on the vitreous samples, which was negative for all infectious entities but positive for poorly differentiated malignant cells. The vitreous biopsy was consistent with the primary endoscopic esophageal biopsy. Ultra-wide view fundus imaging revealed multifocal white intraretinal lesions in the macula and periphery. Optical coherence tomography through these white opacities displayed hyper-reflective inner retinal lesions with no choroidal involvement, suggestive of retinal metastasis. Observation and palliative support was continued until the patient passed away 3 months after diagnosis. Conclusion Retinal metastasis may mimic infectious syndromes such as ARN and are associated with a very poor prognosis. Outside of the retina, no further central nervous system metastasis was found. 5-FU is known to cross the blood–brain-barrier but may be inadequate in preventing retinal metastasis.